A distinctive new species of Genus Neorhegmoclemina Cook (Diptera: Scatopsidae) from Mexico - Huerta, Heron; Dzul, Felipe (Zootaxa, 2015)
A new Neotropical species, Neorhegmoclemina yolotli sp. nov., is described and illustrated based on adult specimens collected in the state of Guerrero, Mexico. This species exhibits features not previously recognized for the genus.